Fluazuron Influences the in vitro Production Embryos of Wagyu Cow - Silva, Vinicius Eduardo Gargaro; Cavalieri, Fábio Luiz Bim; Andreazzi, Márcia Aparecida; Gonçalves, José Eduardo; Santos, José Maurício Gonçalves dos; Moreski, Danieli Aparecida Bóbbo; Mardigan, Laura Paulino; Farias, Tales da Silveira (Journal of Agricultural Studies, 2022)
Imported breeds raised in tropical countries demand greater use of chemical control of ectoparasites, however, this practice can compromise the results of biotechnologies of reproduction. Thus, the objective of this study was to evaluate the presence of chemical residues of tick or their metabolites in the blood and in the follicular fluid and to verify the in vitro embryo production (IVEP) of Wagyu cows, raised in a tropical country, submitted to fluazuron based tick treatment. Twenty adult Wagyu bovine females were used, donors of oocytes, divided into 2 groups: G1 - animals that were not submitted to tick control and G2, animals that were submitted to chemical control of ticks with fluazuron based product (2.5 mg kg-1 of body weight). After application (D0), all cows were submitted to estrous synchronization and, in four moments (D12, D33, D54 and D75) the aspirations of the follicular fluid from the dominant follicles were performed, the oocytes were collected for IVEP and were collected blood samples for extraction and analysis of the presence of chemical residues, using GC-MS. Plasma residues of fluazuron were detected up to 54 days after application of the tick, but no residues were detected in the follicular fluid. Group 1 had a higher number of total and viable oocytes (p<0.0001), however, the viability rate and the blastocyst rate was lower (p<0.0001), showing that the use of ticks compromised IVEP.